Neural circuits mediating visual flight control in flies. I. Quantitative comparison of neural and behavioral response characteristics - Hausen, K (J Neurosci, 1989)
The motion-sensitive horizontal cells in the lobula plate of the fly are assumed to play a key role in the sensory control of yaw torque generated by the flying animal during course-stabilization maneuvers and the fixation of objects. This inference results from comparisons of electrophysiological data obtained from blowflies (Calliphora erythrocephala) and behavioral data obtained mainly from houseflies (Musca domestica) and fruitflies (Drosophila melanogaster). Apart from few exceptions, the compatibility of these physiological and behavioral data has not been critically tested. In the present study, the responses of the equatorial horizontal cell HSE of Calliphora and the yaw torque responses of Calliphora and Musca were recorded under identical visual stimulation with moving periodic gratings. The goal of the experiments was to obtain electrophysiological and behavioral data on Calliphora, on the one hand, and behavioral data on Calliphora and Musca, on the other hand, that allow direct comparisons between the physiological properties of the HSE and the visually induced torque responses in both species. The dependence of the HSE responses and the yaw torque responses on the direction, contrast frequency, and brightness of a moving periodic grating were evaluated quantitatively. The results of the electrophysiological recordings and torque measurements are in close agreement and thus represent strong evidence that the horizontal cells are, in fact, involved in yaw torque control in both species. Measurements of the cellular and behavioral responses as function of the stimulus position in the visual field, however, reveal differences between the spatial sensitivity of the horizontal cells and the sensory input to the motor system.(ABSTRACT TRUNCATED AT 250 WORDS)